Two-Stage Fermentation of Lipomyces starkeyi for Production of Microbial Lipids and Biodiesel - Le Zhang; Ee Yang Lim; Kai-Chee Loh; Yanjun Dai; Yen Wah Tong (Microorganisms, 2021)
The high operating cost is currently a limitation to industrialize microbial lipids production by the yeast Lipomyces starkeyi. To explore economic fermentation technology, the two-stage fermentation of Lipomyces starkeyi using yeast extract peptone dextrose (YPD) medium, orange peel (OP) hydrolysate medium, and their mixed medium were investigated for seven days by monitoring OD600 values, pH values, cell growth status, C/N ratios, total carbon concentration, total nitrogen concentration, residual sugar concentration, lipid content, lipid titer, and fatty acids profiles of lipids. The results showed that two-stage fermentation with YPD and 50% YPD + 50% OP medium contributed to lipid accumulation, leading to larger internal lipid droplets in the yeast cells. However, the cells in pure OP hydrolysate grew abnormally, showing skinny and angular shapes. Compared to the one-stage fermentation, the two-stage fermentation enhanced lipid contents by 18.5%, 27.1%, and 21.4% in the flasks with YPD medium, OP medium, and 50%YPD + 50%OP medium, and enhanced the lipid titer by 77.8%, 13.6%, and 63.0%, respectively. The microbial lipids obtained from both one-stage and two-stage fermentation showed no significant difference in fatty acid compositions, which were mainly dominated by palmitic acid (33.36–38.43%) and oleic acid (46.6–48.12%). Hence, a mixture of commercial medium and lignocellulosic biomass hydrolysate could be a promising option to balance the operating cost and lipid production.